Triple Cross-Linked Hyaluronic Acid Based on Tri-Hyal Technique Has More Durable Effect on Dermal Renewal - Chen R (Clinical, Cosmetic and Investigational Dermatology, 2022)
Rong Chen,1 Wenbin Yang,2 Jing Sun,3 Yuan Liu,4 Qing An,2 Feijuan Zhang,2 Zhuanli Bai,5 Qi Luan2 1College of Life Sciences, Northwest University, Xi’an, 710069, People’s Republic of China; 2Department of Dermatology, Xi’an No.3 Hospital, the Affiliated Hospital of Northwest University, Northwest University, Xi’an, 710069, People’s Republic of China; 3Department of Anesthesiology, Northwest Women’s and Children’s Hospital, Xi’an, 710061, People’s Republic of China; 4Center of Medical Genetics, Northwest Women’s and Children’s Hospital, Xi’an, 710061, People’s Republic of China; 5Department of Plastic and Aesthetic Maxillofacial Surgery, the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of ChinaCorrespondence: Qi Luan, Department of Dermatology, Xi’an No.3 Hospital, the Affiliated Hospital of Northwest University, Northwest University, Xi’an, 710069, People’s Republic of China, Tel/Fax +86-29-61816090, Email luanq@sina.com Zhuanli Bai, Department of Plastic and Aesthetic Maxillofacial Surgery, the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China, Email zhuanlibai@xjtu.ecu.cnBackground: Hyaluronic acid (HA)-based fillers are applied to treat facial wrinkles and volume loss. Many efforts have been made to improve properties of HA to prolong the duration in aesthetic indications. A new cross-linking technique called “Tri-Hyal”, could make HAs to achieve desired rheological characteristics. HAs synthesized by Tri-Hyal are triple cross-linked and sustained-release, which could increase duration of promoting skin rejuvenation after injection.Purpose: To evaluate the efficiency and persistence of HAs with Tri-Hyal on skin rejuvenation and further investigate underlying mechanisms, we compared the performances of cross-linked HA (AF) based on Tri-Hyal with another highly acceptable HA filler (Res) in vivo and in vitro.Methods: Male BALB/c mice were divided into three groups, treated with AF, Res and vehicle, respectively. Skin biopsies were taken on day 0, 30, 90 and 180 after injection and hematoxylin and eosin (H&E), Masson’s trichrome (MT), immunohistochemical (IHC) stainings for CD31, TGF-β and MMP9 were performed. EdU incorporation, cell counting kit-8 (CCK-8), SA-β-Gal staining and activity were measured by biochemical analysis. RFP-GFP-LC3 adeno virus was used for autophagic flux detection. Protein levels of CD44, P62 and LC3I/II were detected by Western blot. Reactive oxygen species (ROS) level was detected by flow cytometry with DCFH-DA probe.Results: The AF synthesized by Tri-Hyal showed persistent dermal structural correction without attenuation up to 6 months, which was illustrated by skin thickness, formation of elastic fibers and vascular density. Consistently, in fibroblasts the AF improved cell proliferation and slowed the senescent in vitro. Furthermore, it promoted cellular autophagy to reduce ROS level, which would account for its function in skin renewal.Conclusion: The HA with Tri-Hyal could stimulate the production of extracellular matrix components more persistently than traditional HA fillers. In terms of mechanisms, it delayed senescence in dermal fibroblasts through reducing oxidative stress mediated by induction of autophagy.Keywords: skin rejuvenation, fibroblasts, senescence, ROS, autophagy